MOBILE EQUIPMENT FOR HELPING POTATO (Solanum tuberosum L.) HARVESTING - Freitas, G. J.; Souza, J. P.; Roque, J. C.; Marchiori, P. S.; Franco, T. N.; Marques, V. C.; Nääs, I. A.; Silva, M. C. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The production of potatoes was introduced in Brazil primarily in the South of the country where the climatic conditions were more favorable for its production. From the beginning of the 21st century, production expanded to São Paulo and Minas Gerais. The potato is an edible tuber, rich in starch and carbohydrates, being relevant to the Brazilian economy and its productivity in the country is growing. The objective of this work was to present a solution for small producers who wish to invest in improving potato picking conditions, with the main focus of increasing the today’s efficiency of the worker of 13.3% of the amount the farmer spends today in labor cost and the increase of 33% in relation to the working time in the field, reducing the painfulness and improving the health of the workers. For the development and structuring of the prototype, data were collected from the field of tuber cultivation. The load on the prototype was tested using stress simulation applied to the components. A mobile equipment has been developed that aims to increase crop productivity by facilitating the harvesting of the tuber. This machine has mechanisms that facilitate the picking process of potatoes in the field. The implementation of the equipment was aimed at reducing the postural stress risk of workers in this activity.